A potent malaria vaccine based on adenovirus with dual modifications at Hexon and pVII - Shiratsuchi, Takayuki (Vaccine, 2017)
Adenovirus (Ad) is thought to be one of the most promising platforms for a malaria vaccine targeted against its liver stages, because of its ability to induce a strong T-cell response against a transgene. However, a further improvement of this platform is needed in order to elicit another arm of the immunity, i.e. humoral response, against malaria. In order to augment immunogenicity and protective efficacy of Ad-based malaria vaccine, we inserted B cell, as well as CD4+ T cell, epitopes of Plasmodium falciparum circumsporozoite protein (PfCSP) into the capsid protein, Hexon, and the core protein, VII (pVII), of Ad, respectively, in addition to the PfCSP transgene. Insertion of PfCSP-derived B cell epitope to Hexon significantly enhanced the epitope-specific antibody response compared to AdPfCSP, an Ad vaccine expressing only PfCSP transgene. PfCSP-derived CD4+ T cell epitope insertion into pVII augmented not only PfCSP-specific CD4+ T cell response but also anti-PfCSP antibody response. Finally, mice immunized with AdPfCSP having both Hexon and pVII modifications were more protected than AdPfCSP or Hexon-modified AdPfCSP against challenge with transgenic rodent malaria parasites expressing the PfCSP. Overall, this study has demonstrated that Hexon and pVII-modified AdPfCSP vaccine is a promising malaria vaccine which induces strong PfCSP-specific humoral, CD4+ T cell, and CD8+ T cell responses and protects against infection with transgenic malaria parasites expressing the PfCSP.